Outcome of patients with systemic diseases admitted to the medical intensive care unit of a tertiary referral hospital: a single-centre retrospective study. (3rd March 2016) - Heijnen, T; Wilmer, A; Blockmans, D; Henckaerts, L
Abstract : Objectives : Systemic diseases form a rare heterogeneous group of diseases, with important morbidity caused by disease evolution and/or treatment. We describe the clinical features and outcome of patients with these diseases admitted to a referral hospital intensive care unit (ICU). Method : We conducted a retrospective case review of all patients with systemic diseases (n = 86) admitted to the medical ICU of Leuven University Hospital between May 2007 and September 2012. Results : The most frequent diagnoses were systemic vasculitis (n = 31), sarcoidosis (n = 15), systemic sclerosis (n = 9), and systemic lupus erythematosus (SLE) (n = 7). The main reason for admission was infection (60%), followed by disease-related organ failure (48%). Respiratory failure was the most common organ dysfunction. The mean APACHE II (Acute Physiology and Chronic Health Evaluation II) score was 28 ± 10. Mortality was 19% during ICU admission, 39% during hospital stay, and 58% at the end of follow-up. Death was caused by infection in the majority of cases (56%), and by evolution of the underlying disease in 32%. Only age and APACHE II score were associated with mortality. Conclusions : The mortality of patients with systemic diseases admitted to an ICU is high, both during their stay in the ICU and afterwards. Age and APACHE II score, but not infection or immunosuppressive therapy, were associated with mortality.